Biofilm and membrane biofouling control with microbubbles - Ashutosh Agarwal (2014)
Bacterial attachment onto surfaces is the first step towards the formation of complex 3-dimensional biofilm, while it is also responsible for development of membrane biofouling which results in significant decline in water flux and increase in trans-membrane pressure. To mitigate membrane biofouling, physic-chemical cleaning methods have often been practiced. However, chemical cleaning of membrane not only degrade the membrane surface structure, but also generate carcinogenic byproducts upon reaction with the organic matters present in water. Hence, this study explored the potential of self-collapsing microbubbles (MBs) for biofilm/biofouling control.